A pilot study of secondary teachers' understanding of population dynamics - Hockey, Athol James Temlett (Rhodes University, Faculty of Education, Department of Education, 1996)
Population dynamics is a South African secondary school biology syllabus topic which deals specifically with ecology or concepts within the realm of ecology. It is currently taught in a way which largely emphasises the teaching and learning of facts and concepts, often out of any context to which students can relate. While it is important to convey scientific concepts, it is just as important to address social and political issues regarding overpopulation and the environment. This research involved the administration of a questionnaire to Std 10 biology teachers in the Department of Education and Training (DET), which sought to obtain information about various aspects of teachers' teaching of population dynamics. These included their feelings toward the teaching of the specific sections of the population dynamics syllabus, and their knowledge and views of environmental issues and human population expansion. The findings of the research suggest that population dynamics is an important topic for students to learn about. The traditional teacher-centred approach to teaching is used by the teachers in the research sample. The sections considered by the teachers to be most important for learning were also considered the most interesting and the easiest to teach. The majority of the teachers in the research sample recognised that human population growth is a global and local problem and that South Africa cannot sustain its present population growth. The teachers in the sample show a diversity of opinions about sustainable development, and have a limited understanding of the links between population, poverty and consumption. Important information gained from the research will be significant in the development of a teaching and learning module on population dynamics that reflects the aims and purpose of environmental education.
Keywords: Environmental education -- South Africa; Population -- Study and teaching (Secondary) -- South Africa